1989
DOI: 10.1002/jat.2550090310
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of toxicity involving haemorrhage and cardiovascular failure, caused by parenteral administration of a soluble polyacrylate in the rat

Abstract: Adverse effects, involving a combination of hypotension and widespread haemorrhages, as well as evidence of vascullar and other tissue dissociation, associated with various systemic malfunctions (cyanosis, cardiac arrhythmias, neuromuscular disorder and death) were observed in the rat, from parenteral administration of a high-molecular-weight soluble polymer, sodium polyacrylate (EN21). Experiments to elucidate the mechanism of this effect involved comparisons with a low-molecular-weight sodium polyacrylate (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…administration could be attributed to hypocalcaemia produced by an ionic exchange reaction occurring between calcium and magnesium ions. Hicks et al (1989) found the same behaviour after i.p., i.v. and s.c. administration of a sodium polyacrylate polymer at doses ranging from 5 to 100 mg/kg, suggesting that localization of the viscous, high-molecular-weight material in vascularized compartments, together with its known ability to form insoluble precipitates with calcium, led to the operation of a calcium sink resulting in hypocalcaemia which would explain the haemorrhages as well as neuromuscular and cardiac malfunctions observed in the said study.…”
Section: Tablesupporting
confidence: 77%
See 1 more Smart Citation
“…administration could be attributed to hypocalcaemia produced by an ionic exchange reaction occurring between calcium and magnesium ions. Hicks et al (1989) found the same behaviour after i.p., i.v. and s.c. administration of a sodium polyacrylate polymer at doses ranging from 5 to 100 mg/kg, suggesting that localization of the viscous, high-molecular-weight material in vascularized compartments, together with its known ability to form insoluble precipitates with calcium, led to the operation of a calcium sink resulting in hypocalcaemia which would explain the haemorrhages as well as neuromuscular and cardiac malfunctions observed in the said study.…”
Section: Tablesupporting
confidence: 77%
“…Moreover, there were no significant changes in body weight, food consumption or visual organ examination (liver, spleen, lungs, kidney, stomach and intestine). The same behaviour was obtained by Hicks et al (1989) after oral administration of a 100 mg/kg dose of sodium polyacrylate polymer to rats. It must be noted that the dose ranges tested in our study are much wider than the one reported by Hicks et al (1989).…”
Section: Tablesupporting
confidence: 59%
“…SPA is an intensely hydrophilic anionic polymer that has significant osmotic activity [ 20 , 33 ]. Previous investigations have demonstrated local and systemic toxicity of variable severity with parenteral, enteral, and intratracheal SPA administration in animals [ 34 , 35 ]. Given the evidence of alveolar epithelial cytotoxicity and the histological evidence of alveolar inflammation presented here, we cautiously speculate that SPA caused ARDS through direct injury to the alveolar epithelium, potentially through the creation of an osmotic gradient across the alveolar epithelial membrane.…”
Section: Discussionmentioning
confidence: 99%
“…There is definitely a need for additional adjuvants that could be safely used in humans, would be easy to source and to formulate with a wide range of antigens and would be broadly applicable to a wide range of vaccines. In this regard, different studies indicated that polyacrylates (PAAs) in different forms and formats were safe and biocompatible and adjuvant active within a range of polymer sizes, doses, formulations and routes of administration compatible with vaccination ( Coucke et al, 2009 ; Cranage et al, 2011 ; De Clercq, 2010 ; Diamantstein et al, 1971 ; Gartlan et al, 2016 ; Hicks et al, 1989 ; Krashias et al, 2010 ; Kreuter and Haenzel, 1978 ; Mustafaev, 1996 ; Parker et al, 2009 ; Powell et al, 2015 ; Regelson, 1979 ; Wegmann et al, 2015 ; Zondlo Fiume, 2002 ). Among the adjuvant-active PAAs, one can find plain PAAs ( Diamantstein et al, 1971 ; Hilgers et al, 1998a ), PAA dendrimers ( Zaman et al, 2010 , 2011 ), PAA alkyl esters ( Hilgers et al, 2000 , 1998b ; Tifrea et al, 2011 ) and the crosslinked PAAs ( i.e.…”
Section: Introductionmentioning
confidence: 99%